The retrospective study for effectiveness of cervical cerclage in preventing recurrent preterm birth - Rie Seyama; Shintaro Makino; Jun Takeda; Satoru Takeda; Atsuo Itakura (Elsevier, 2022)
Objective: This study aimed to clarify the effectiveness of cervical cerclage in preventing recurrent preterm births. Materials and methods: A retrospective study was conducted using the perinatal registration database of the Japan Society of Obstetrics and Gynecology for the Perinatal Center from 2014 to 2016. The efficacies of history-indicated, ultrasound-indicated, and physical examination-indicated cerclage as preventive treatments for women with a history of preterm birth were evaluated by comparing cerclage and non-cerclage cases. Fisher's exact test was performed to evaluate any significant differences in patient backgrounds. Prior to the evaluation, propensity score matching was performed for history-indicated and ultrasound-indicated cerclage patients. Results: For this study, 6060 multiparous women with a history of preterm birth were reviewed. After excluding 17 patients with unknown indications for cervical cerclage, 6043 patients were included in the study. History-indicated and ultrasound-indicated cerclage did not reduce the risk of preterm birth in subsequent pregnancies for any of the pregnancy periods (p = 0.413, p = 1.000). In contrast, physical examination-indicated cerclage significantly reduced the risk of subsequent preterm births for all pregnancy periods (p < 0.001). Conclusion: Subsequent preterm births were effectively prevented only in physical examination-indicated cerclage cases. For history- or ultrasound-indicated cerclage, statistically significant differences in subsequent preterm births were not evident.